A case report of peri-ovarian hematoma and hemoperitoneum following ovum pickup: a laparoscopic intervention - Nikita; Basheer, Sanam; Praveen, Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
A 29-year-old nulligravida woman with a seven-year history of primary infertility underwent transvaginal oocyte pick-up (TV-OPU) following controlled ovarian stimulation for in vitro fertilization (IVF) with intracytoplasmic sperm injection (ICSI). Post-procedure, she presented with abdominal pain and bilateral flank tenderness. There was significant haemoglobin drop and ultrasonography showed evidence of peri-ovarian hematoma. Initial conservative management, including close monitoring and intravenous antibiotics, was implemented; however, progressive haemodynamic compromise and hematoma expansion necessitated diagnostic laparoscopy. Intraoperatively, a right-sided peri-ovarian hematoma and active bleeding from the right ovarian puncture site were identified and surgically managed. The patient demonstrated an uneventful postoperative recovery and was discharged on day six. This case underscores the importance of vigilant monitoring, individualized management, and timely surgical intervention for post-TV-OPU complications.